DEVELOPING PERFORMANCE MANAGEMENT SYSTEM WITH BALANCED SCORE CARD APPROACH: A CASE STUDY OF PT. SMART-MODULAR BUILDING INDONESIA - Elia Oey; Daniel Tommiki; Fachrun Nisaa Widyastuti (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Performance Measurement System (PMS) is essential for any organization, as it serves as guiding compass for continuous improvement. The research is a case study in a modular concrete company refining their current PMS using Balanced Score Card approach. The research developed Balanced Score Card starting from the whole company level, and then cascaded down into 3 main company activities, design, supply and construction. Measurement for 1st quarter of 2019 was done, and target and action plans for each activity were also set for the studied company